Enhancing Educational Quality: A Prototype System for Evaluating Faculty Performance in Higher Education - Agrawal, Renuka; Sharma, Kanhaiya (Journal of Engineering Education Transformations, 2025)
Ensuring educational quality in higher education is a global concern transcending borders, including India. Nations worldwide recognize the significance of teaching faculties in enhancing their educational institutions' prestige. Consequently, there is a growing emphasis on retaining and motivating faculty members to elevate their institutions to worldclass standards. This necessitates the periodic evaluation of faculty performance to gauge the overall educational institute's effectiveness. Continual monitoring of institute quality and the teachinglearning process is imperative for sustaining educational standards. In essence, the responsibility lies with teaching faculties nationwide to impart the right skills and knowledge to students. Expert guidance and constructive feedback from mentors are pivotal in students' skill development and knowledge enrichment. Students greatly value faculty members who support and inspire them throughout their arduous academic journeys. This research paper introduces a prototype system designed to assess, evaluate, and provide recommendations for faculty performance within educational institutions. The proposed system aims to contribute to the ongoing efforts to enhance educational quality and faculty effectiveness.